ANALISA REALIBILITY DAN MAINTAINABILITY PADA MESIN SCREW PRESS DENGAN MENGGUNAKAN METODE DISTRIBUSI NORMAL DI PABRIK KELAPA SAWIT - Benita Septiana Sinaga; Zulham Effendi; Giyanto (Institut Teknologi Sawit Indonesia (ITSI), 2019)
The cessation of the processing process at the palm oil mill will cause losses to the company, which can result inlow productivity of the plant. Damage to equipment at the palm oil mill requires more costs to repair the damage.For this reason, good maintenance is needed for each equipment used in the processing process using the normaldistribution method. In this study the tool used was Screw Press. The purpose of this study was to determine thevalue of Realibility and Maintainabiity by using a normal distribution and to determine the cause of damage to theScrew Press machine. This research stage was carried out by taking data on damage and repair of Screw Press inApril-June 2017 and processing data using normal distribution. The data needed in normal distribution is the valueof Realibility, Maintainability, and standard devisia. By doing this data processing, the Screw Press machine canoperate well with reliability value in April-June 2017 on screw press 1 machines at 98%, 98%, 99% andmaintainability value of 21.78 hours, 18.8 hours, 19 , 18 hours. Whereas in screw press machine 2 in April - June2017 the reliability value is 99%, 98%, 95% and the Maintainability value is 19.9 hours, 18.68 hours and 18 hours.